Ethnobotanical role of sago in wetland biodiversity and resilience in the Riau Archipelago, Indonesia - TISRIN MAULINA DEWI; WORO SUMARNI; SAIFUL RIDLO; ADITYA MARIANTI (Society for Indonesian Biodiversity, 2025)
Abstract. Dewi TM, Sumarni W, Ridlo S, Maryanti A. 2025. Ethnobotanical role of sago in wetland biodiversity and resilience in the Riau Archipelago, Indonesia. Biodiversitas 26: 6232-6239. Sago (Metroxylon sagu) is a tropical plant that plays an important role in wetland ecosystems and socio-economic resilience in Indonesia, particularly in the Riau Islands. This study aims to explore the role of sago ethnobotany in supporting biodiversity and ecosystem resilience in two locations, Musai (Lingga) and Alai (Karimun), and to identify how local wisdom-based sago management contributes to the conservation of the wetland ecosystem. The research approach employed was qualitative, semi-structured interviews (n = 40) with informants from various categories, including community leaders, traditional processors, farmers, and traditional leaders. Participatory observation was also conducted to explore local knowledge about sago management. The results showed that sago plays a dual role, serving as both a food source and economic commodity, and contributes to ecosystem management through management practices based on traditional ecological knowledge, such as crop rotation and selective pruning. Ethnobotanical index analysis shows that sago has the highest use value in the food category (UV = 1.00) and household economy/trade (UV = 0.63). This sago management also supports the achievement of Sustainable Development Goals (SDGs), particularly SDG 13 (Climate Action) and SDG 15 (Life on Land), by increasing carbon sequestration capacity and preserving wetland ecosystems. Strengthening local sago-based management and integrating traditional practices into wetland policy frameworks are essential for achieving both livelihood security and biodiversity conservation in the Riau Archipelago.